Assessment of Age and Sex Difference in Cardiopulmonary Function of Children and Adolescents with Ventricular Septal Defect - Chao-Ruei Lin; Ya-Fen Liu; I-Ching Huang; Yi-Jen Chen; Chia-Hsin Chen; Ko-Long Lin (Journal of Cardiovascular Development and Disease)
In the past, an isolated ventricular septal defect (VSD) was categorized as a simple lesion with assumed negligible long-term risks when treated correctly in childhood; however, evidence has suggested that patients with isolated congenital VSDs carry a substantial burden of cardiovascular morbidity throughout life. This study aimed to investigate the cardiopulmonary function (CPF) in isolated VSD patients of a young age and the relationship of CPF with age, sex and body mass index (BMI). This retrospective cohort study was conducted at a tertiary medical center in southern Taiwan. We recruited children and adolescents (aged 5 to 18 years) with isolated VSDs who underwent the symptom-limited treadmill exercise test. Data from 289 children and adolescents (157 males, 132 females) were included in the analysis. The participants were stratified into three groups according to age. The male patients had a significantly higher oxygen uptake at the anaerobic threshold (AT VO2) and a higher peak oxygen uptake (peak VO2) (all p < 0.05). Normalized AT VO2 (mL/kg/min) and normalized peak VO2 (mL/kg/min) were significantly negatively associated with BMI. In conclusion, male patients with isolated VSDs had similar or better CPF compared with female patients. BMI had a negative association with CPF in young VSD patients.